Optimization of Naringin Extraction, Synthesis of Dihydrochalcone and Its Effects on Reducing Blood Lipid Levels In Vitro - Xiaolei Yu; Haowei Wu; Lei Zhang; Dongliang Fei (Molecules)
Response surface methodology (RSM) was used to optimize the extraction process of naringin. The central component design included three parameters of extraction, namely temperature (X1), solid–liquid ratio (X2), and extraction time (X3). The optimum extraction temperature was 67 °C; the ratio of feed to solvent was 54:1 mL/g, and the extraction time was 2.8 h. According to the best extraction conditions, naringin was processed to verify the accuracy of the model. Five parallel experiments were set up, and a yield of 3.248% naringin was obtained, which was equivalent to the predicted yield of 3.256%. Naringin was purified to obtain naringin-refined products using DM101 macroporous adsorption resin. Naringin dihydrochalcone was synthesized following catalytic hydrogenation of purified naringin. The structures of naringin and naringin dihydrochalcone were determined via Fourier infrared spectrometer and nuclear magnetic resonance spectrometry. In vitro determination of the lipid-lowering activity of naringin dihydrochalcone was also conducted. Further focusing on HepG2 cells, a high cholesterol-induced high-fat HepG2 cell model was established. We measured the effects of different concentrations of naringin dihydrochalcone on intracellular lipids in denatured HepG2 cells and further validated the lipid-lowering effect of naringin at the cellular level. The results showed that naringin dihydrochalcone has a potential application in functional foods for lowering blood lipids.